STUDI LITERATUR : PENGARUH ASPEK KARASTERISTIK CEO TERHADAP KEBERHASILAN KINERJA KEUANGAN PERUSAHAAN START UP - Zulkarnaen, Have (Pro-fit, 2024)
This literature study explains how the influence of CEO characteristics on the success of start-up company financial performance is an attempt to understand the complex dynamics in a sustainable and rapidly changing business environment, how do CEO characteristics affect business direction, strategy, vision, and mission that are manifested in a company's performance. In this study, we explore various theories and relevant empirical findings to identify factors that influence the financial performance of start-up companies led by CEOs. The theoretical review includes the Big Five Personality Traits Theory, Leadership Style Theory, and Experience and Education Theory, each of which provides valuable insights into the relationship between individual CEO characteristics and company performance. Our analysis highlights the importance of CEO personality characteristics, leadership style adopted, and experience and education in shaping the success of start-up companies. We find that there is no single formula for becoming a successful CEO in the start-up context; instead, the success of company performance is influenced by a combination of these factors.